On Pedagogy, Trauma and Difficult Memory: Remembering Namatjira, our Beloved - McConaghy, Cathryn (The Australian Journal of Indigenous Education, 2003)
Abstract One of the projects engaged in within the text Rethinking Indigenous Education(RIE) (McConaghy, 2000) was an analysis of the colonial regimes that are reproduced within Indigenous education, often despite our emancipatory intentions. Through a detailed critique of the various competitions for epistemic authority in the field, the book explores the structural processes by which certain knowledges are legitimated as “truths” and the material and symbolic effects of these.The focus of the book was on the imagined worlds of various traditions of knowing Indigenous education and their claims to authority. It was a “how” rather than a “who” story that dealt with theoretical assumptions, broad-brush policy and curriculum inquiry and that attempted to avoid the identity politics that had gripped Indigenous education for more than a decade. Importantly the book also suggested that rather than being cumulative, critique is a process that needs to be ongoing, done again and again. This paper, Remembering Namatjira, has sought to move beyond the main projects of RIE, many of them structural in nature, to an analysis of more intimate aspects of Indigenous education. It addresses some of the “who” issues, not in terms of representation politics, who can know and speak what, but in terms of the psychic difficulties that we attach to knowledge in Indigenous education. Whereas RIE drew upon postcolonial and feminist insights, this paper considers the contribution of psychoanalysis to thinking through some of the more intractable issues that remain unexamined or underexamined in the field. Among the issues addressed are the fundamental dilemmas around our ambivalences in education; the notion of pedagogical force (and transferences, resistances and obstacles to learning); the work of ethical witnessing; and issues of difficult knowledge, or knowledge and memories that we cannot bear to know. Central to the work of rethinking Indigenous education again, in moving beyond deconstruction, is the process of making meaning out of the ruins of our lovely knowledges (Britzman, 2003), our comfort knowledges, about what should be done in Indigenous education.